Family happiness and college students’ smartphone addiction control: the chain mediation effect of emotion regulation and self-control - Yin, Xiangju; Yu, Yongli; Qian, Hongwei; Wang, Zixu (Frontiers in Public Health, 2024)
Background More and more college students use smartphones for a long time every day. The problem of smartphone addiction has become a hot topic of social concern. It not only affects the physical and mental health of college students but also affects the development of families and society. To investigate the effect of family happiness on college students’ smartphone addiction, we conducted a questionnaire survey and analysis. Methods In this study, 214 college students were investigated using the adolescent family happiness questionnaire, college students’ smartphone addiction scale, self-control scale, and emotion regulation scale. The data were analyzed by Amos and SPSS26.0 software. Results The results showed that: (1) Family happiness, emotion regulation, and self-control were significantly inversely correlated with smartphone addiction; (2) Emotion regulation and self-control served as partial mediators in the linkage between family happiness and smartphone addiction, and the chain mediation effect of emotion regulation and self-control was significant. Conclusion Family happiness, emotion regulation, and self-control are key factors that significantly influence college students’ smartphone addiction behavior. Family happiness not only has a direct effect on college students’ smartphone addiction behavior but also has an indirect effect on it through the chain mediation effect of emotion regulation and self-control.